Population Pharmacokinetics of Amoxicillin in Term Neonates Undergoing Moderate Hypothermia. Issue 3 (13th October 2017) - Bijleveld, YA; Mathôt, RAA; van der Lee, JH; Groenendaal, F; Dijk, PH; van Heijst, A; Simons, SHP; Dijkman, KP; van Straaten, HLM; Rijken, M; Zonnenberg, IA; Cools, F; et al.
Abstract : The pharmacokinetics (PK) of amoxicillin in asphyxiated newborns undergoing moderate hypothermia were quantified using prospective data ( N = 125). The population PK was described by a 2‐compartment model with a priori birthweight (BW) based allometric scaling. Significant correlations were observed between clearance (Cl) and postnatal age (PNA), gestational age (GA), body temperature (TEMP), and urine output (UO). For a typical patient with GA 40 weeks, BW 3, 000 g, 2 days PNA (i.e., TEMP 33.5°C), and normal UO, Cl was 0.26 L/h (interindividual variability (IIV) 41.9%) and volume of distribution of the central compartment was 0.34 L/kg (IIV of 114.6%). For this patient, Cl increased to 0.41 L/h at PNA 5 days and TEMP 37.0°C. The respective contributions of both covariates were 23% and 27%. Based on Monte Carlo simulations we recommend 50 and 75 mg/kg/24h amoxicillin in three doses for patients with GA 36–37 and 38–42 weeks, respectively.